Johnny's broadforks [library of things] : model 727 (Johnny's Garden Seeds, 2019)
"Aerating the soil with your broadfork once a year will greatly enhance to long-term productivity of the soil. Work backwards down the bed to avoid stepping on the freshly worked area. With the tines on the side of the fork facing you, press the fork into the soil by stepping on the crossbar. Pull back on the handles approximately 45 degrees as you step backwards off the crossbar and lift the broadfork out of the soil."-- instruction sheet